2021
DOI: 10.1002/app.51543
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal and solar properties of perlite coated woven fabrics

Abstract: In this study, thermal insulation and solar properties of polyester woven fabrics which were coated with micronized perlite having three different particle sizes (10–38, 50–63, and 100–150 μm) at four different concentrations (20, 40, 60, and 80 g/kg) were investigated. The coating process was performed according to the knife‐over‐roll method. Thermal measurements were carried out with two different principles to evaluate contact and radiant heat transfer according to JIS R 2618 (testing method for thermal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…The test results showed that both pads without added thymol and antimicrobial pads had good water absorption, with water absorption values of 0.136 ± 0.004 g/cm 2 and 0.142 ± 0.006 g/cm 2 , respectively, indicating that the addition of thymol does not affect the water absorption because it is the intermediate layer (SAP) that has the water absorption properties, and Özan, Kanik and Özer [44] demonstrated that the highly absorbent resins have good water absorption. Therefore, it is shown that the antimicrobial pads can absorb the drip loss of meat during storage and not only maintain the water absorbency of the original pads but also have antimicrobial properties.…”
Section: Water Absorption Test Of Antibacterial Padsmentioning
confidence: 99%
“…The test results showed that both pads without added thymol and antimicrobial pads had good water absorption, with water absorption values of 0.136 ± 0.004 g/cm 2 and 0.142 ± 0.006 g/cm 2 , respectively, indicating that the addition of thymol does not affect the water absorption because it is the intermediate layer (SAP) that has the water absorption properties, and Özan, Kanik and Özer [44] demonstrated that the highly absorbent resins have good water absorption. Therefore, it is shown that the antimicrobial pads can absorb the drip loss of meat during storage and not only maintain the water absorbency of the original pads but also have antimicrobial properties.…”
Section: Water Absorption Test Of Antibacterial Padsmentioning
confidence: 99%
“…The chemical composition of perlite is approximately composed of 75% SiO 2 with oxides of (14.8%), K (4.8%), Na (2.9%), Ca (0.9%), Mg (0.1%), Fe 2 0 3 (1.5%) and bound water (3.0%). When perlite particles are heated rapidly to temperatures exceeding 870 °C (1600 °F), they expand to 4-20 times of their original volume [25]. The specific characteristics of the expanded perlite are the following: 50~250 (density, mg/cm 3 ), 0.03~0.05 (thermal conductivity, W/ (m•K)), and -200~800 (service temperature, °C) [26].…”
Section: Perlite As Flame-retardant Filler For Textile Materialsmentioning
confidence: 99%
“…Son yıllarda yaşanan enerji sıkıntıları ve fosil yakıtların neden olduğu çevresel sorunlar (karbon salınımının artması gibi) tüm dünyayı çeşitli arayışlara ve önlemler almaya yöneltmiştir. Bunlardan birisi de enerjiyi tasarruflu kullanmak amacıyla gerek üretimde ve gerekse yaşam alanlarında enerji kayıplarının en aza indirilmesi konusudur [1]. Isı kaybının en fazla olduğu alanın ise evsel ısınma ve endüstriyel ısı kayıplarından kaynaklandığı düşünülmektedir.…”
Section: Introductionunclassified